2011
DOI: 10.1103/physrevb.84.064439
|View full text |Cite
|
Sign up to set email alerts
|

Thermal relaxation rates of magnetic nanoparticles in the presence of magnetic fields and spin-transfer effects

Abstract: We have measured the relaxation time of a thermally unstable ferromagnetic nanoparticle incorporated into a magnetic tunnel junction (MTJ) as a function of applied magnetic field, voltage V (-0.38 V < V < +0.26 V), and temperatures (283 K< T< 363 K) . By analyzing the results within the framework of a modified Néel-Brown formalism we determine the effective attempt time of the nanoparticle and also the bias dependences of the in-plane and out-of-plane spin transfer torques. There is a significant linear modifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…They can be used to generate random bits at kHz frequencies, sufficient for real-time brain-inspired systems like 7 , but not for high performance applications. In our 50 × 150nm superparamagnetic tunnel junctions, we identified that the switching occurs through nucleation and propagation of a magnetic domain, probably seeded by fluctuations in a subset of grains within it 31 (supplementary information S3). By contrast, recent experiments on perpendicular magnetic anisotropy (PMA) magnetic tunnel junctions have shown that aggressively scaled devices (diameters smaller than 35nm) switch at the scale of the whole volume 34 .…”
Section: Scaling Capabilities Of the Random Number Generators In mentioning
confidence: 99%
See 1 more Smart Citation
“…They can be used to generate random bits at kHz frequencies, sufficient for real-time brain-inspired systems like 7 , but not for high performance applications. In our 50 × 150nm superparamagnetic tunnel junctions, we identified that the switching occurs through nucleation and propagation of a magnetic domain, probably seeded by fluctuations in a subset of grains within it 31 (supplementary information S3). By contrast, recent experiments on perpendicular magnetic anisotropy (PMA) magnetic tunnel junctions have shown that aggressively scaled devices (diameters smaller than 35nm) switch at the scale of the whole volume 34 .…”
Section: Scaling Capabilities Of the Random Number Generators In mentioning
confidence: 99%
“…Unlike the case of MRAMs, for which the magnetization direction of the free magnet is highly stable and can only be switched by proper external action, the magnetization direction of the superparamagnetic free magnet spontaneously switches between its two stable states, due to low stability relative to thermal fluctuations ( Fig. 1(c)) 31,32 . Here, no bias or perturb scheme is required to provoke these random fluctuations, but only temperature.…”
Section: Exploiting the Stochastic Behavior Of Superparamagnetic mentioning
confidence: 99%
“…3 The temperature dependence of  can be understood via the by several orders of magnitude concurring with experimental results. 11 The virtue of our numerically exact solutions of the recurrence relations for the relevant statistical moments is that they hold for the most comprehensive formulation of the generic nanopillar model ( Fig. 1), i.e., for arbitrary directions of the external field and spin polarization and for arbitrary free energy density, yielding the STT switching characteristics under conditions otherwise inaccessible.…”
Section: Vresultsmentioning
confidence: 88%
“…8 Such effects underpin the relatively new subject of spintronics, 9 where the carrier of information is the spin state of a ferromagnetic material. Typical practical applications include very-high-speed current-induced magnetization switching by (a) reversing the orientation of magnetic bits in high density memory structures as opposed to the more conventional Oersted field switching 7,10,11 and (b) using spin polarized currents both to generate and manipulate steady state microwave oscillations with a frequency proportional to the spin-polarization current 12,13 via the steady state magnetization precession. Essentially both objectives (a) and (b) can be achieved because, depending on its sign, the spin current either enhances or diminishes the effective damping representing the microscopic degrees of freedom of a ferromagnetic film 8 (cf.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of an external magnetic field without any read disturb current [26,27], Eq. (2) transforms to…”
Section: Sttram Retention Enhancementmentioning
confidence: 99%